Controlled-Length Efficient Synthesis of Heterobifunctionalized Oligo Ethylene Glycols - Zona, Cristiano; D’Orazio, Giuseppe; La Ferla, Barbara (Synlett, 2013)
A set of heterobifunctional oligo ethylene glycols have been synthesized in a straightforward and stepwise manner starting from inexpensive, commercially available, tetraethylene glycol. Introduction of terminal allyl moieties followed by reductive ozonolysis allowed controlled elongation. Mono-allyl derivatives were used for the elongation with a functionalized moiety and for successive introduction of different functional groups on the chain terminal.
Keywords: ethylene glycols; heterobifunctional; spacers; biomolecule grafting; elongation